Strategies to counteract adverse remodeling of vascular graft: A 3D view of current graft innovations - Tan, Wei; Boodagh, Parnaz; Selvakumar, Prakash Parthiban; Keyser, Sean (Frontiers in Bioengineering and Biotechnology, 2023)
Vascular grafts are widely used for vascular surgeries, to bypass a diseased artery or function as a vascular access for hemodialysis. Bioengineered or tissue-engineered vascular grafts have long been envisioned to take the place of bioinert synthetic grafts or eventually vein grafts under certain clinical circumstances. However, host responses to a graft device induce adverse remodeling, which often depend on graft properties and host’s conditions. Herein, we have mapped out the relationship between the design constraints and outcomes for vascular grafts, by analyzing impairment factors involved in adverse graft remodeling. Strategies to tackle the impairment factors and counteract adverse healing are summarized by outlining the research landscape of graft innovations in three dimensions – cell technology, scaffold technology and graft translation. Such a comprehensive view of cell and scaffold technological innovations in the translational context may benefit the future advancements in vascular grafts.